Inferior Vena Cava Agenesis and Deep Vein Thrombosis in the Young: A Review of the Literature and Local Experience - Tufano, Antonella; Cannavacciuolo, Francesca; Gianno, Adriana; Cerbone, Anna Maria; Mangiacapra, Sara; Coppola, Antonio; Amitrano, Maria (Seminars in Thrombosis and Hemostasis, 2017)
Congenital agenesis of the inferior vena cava (AIVC) is a rare vascular abnormality with a prevalence of 0.0005 to 1% in the general population. This condition is found in almost 5% of young patients (younger than 30 years) with proximal, typically bilateral, deep venous thrombosis (DVT) of the lower limbs, often in the absence of apparent risk factors. However, AIVC in young patients with DVT is probably underestimated because AIVC cannot be detected by the standard DVT diagnostic workup. Inherited thrombophilia has been reported in patients with AIVC-associated DVT, as an additional risk factor, but its role is poorly investigated. The best therapeutic strategy and the optimal duration of anticoagulant treatment of DVT in patients with AIVC are still unclear. Here, we describe 14 young patients (2 females and 12 males, mean age at first DVT: 27.8 ± 10.1 years), with color Doppler ultrasound (US) and abdominal computed tomography scan confirmed AIVC-associated DVT and discuss their characteristics in the framework of a literature review on this topic. Our patients were mainly males (10/12) and experienced proximal DVT events, not complicated by pulmonary embolism. DVT-precipitating factors were detected only in five cases, the two female patients (oral contraceptives and puerperium), and three male patients (one after leg fracture and two after abdominal surgery). Thrombophilic abnormalities were found in eight patients (heterozygous factor V Leiden mutation, n = 3; mild/moderate hyperhomocysteinemia, n = 3; reduced protein C activity, n = 1; antiphospholipid syndrome, n = 1). The majority of patients (13/14) were treated with long-term oral anticoagulant therapy and elastic stockings (ES), with a very low rate of DVT recurrence (1/14, mean follow-up 7 years). These clinical characteristics were largely consistent with those of 161 patients identified by review of the literature. On the whole, although many aspects are still poorly known, our case series and literature review suggest that a search should be undertaken for AIVC in young patients with proximal idiopathic, particularly when bilateral, DVT, which should then be treated with prolonged anticoagulation and ES.
Keywords: agenesis of inferior vena cava; deep vein thrombosis; thrombophilia; anticoagulation